2020
DOI: 10.1007/s13312-020-1958-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Features of Coronavirus Disease 2019 in Moroccan Children

Abstract: Objectives: This study aims to analyze the epidemiological and clinical features of coronavirus disease 19 (COVID-19) in a Moroccan pediatric population. Methods: A retrospective study of a cohort of 74 children with RT-PCR confirmed COVID-19. We collected information on clinical and laboratory features of all children (age <18 years) admitted between 2 March, 2020 and 1 April, 2020. Results: The mean (SD) age of the 74 children (40 girls) was 7 (1.5) years. The mean (SD) time from illness onset to diagnosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…The scholarly literature on the effects of the COVID-19 pandemic on food systems and consumption patterns has been so far mostly geographically biased; it focuses on Western and Southern Europe, North America, and China (30), while developing countries in general and those of the NENA region in particular, such as Morocco, have been overlooked. The analysis of the scholarly literature shows that most of the papers dealing with the COVID-19 emergency in Morocco focus on the dynamics of the spread of the virus as well as its health impacts (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). Other articles analyze the pandemic's socio-economic impacts in the kingdom (45,59).…”
Section: Introductionmentioning
confidence: 99%
“…The scholarly literature on the effects of the COVID-19 pandemic on food systems and consumption patterns has been so far mostly geographically biased; it focuses on Western and Southern Europe, North America, and China (30), while developing countries in general and those of the NENA region in particular, such as Morocco, have been overlooked. The analysis of the scholarly literature shows that most of the papers dealing with the COVID-19 emergency in Morocco focus on the dynamics of the spread of the virus as well as its health impacts (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). Other articles analyze the pandemic's socio-economic impacts in the kingdom (45,59).…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of studies describing the epidemiology and clinical features of COVID‐19 among children in Africa. Of published studies, a relatively small number of children were studied, ranging from 34–1,439 23–25 . Findings from China, 7 Europe, 15 and North America, 19 where the majority of studies of COVID‐19 in children were conducted, may not be generalizable to countries such as South Africa where conditions such as malnutrition, childhood obesity, tuberculosis, HIV infection, or HIV exposure among children are more prevalent and background child mortality rates from other bacterial and viral infections are higher than other countries 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…The commonest otorhinolaryngological symptom was cough, followed by sore throat and nasal discharge. Previous reviews 109 have revealed the commonest presenting symptoms in children to be fever (pooled prevalence of 51 per cent; 95 per cent CI = 45-57) and cough (pooled prevalence of 41 per cent; 95 per cent CI = [35][36][37][38][39][40][41][42][43][44][45][46][47]. By comparison, the commonest otorhinolaryngological symptoms noted in adult patients, by Qiu et al, 110 were olfactory dysfunction (47 per cent), sneezing (27 per cent) and nasal congestion (19 per cent).…”
Section: Discussionmentioning
confidence: 99%